Virtue and Asceticism. (28th August 2018) - Besong, Brian
Abstract: Although one can find a robust philosophical tradition supporting asceticism in the West, from ancient Greece to at least early modernity, very little attention has been paid to what motivated this broad support. Instead, following criticism from figures such as Hume, Voltaire, Bentham, and Nietzsche, asceticism has been largely disregarded as either eccentric or uniquely religious. In this paper, I provide what I take to be the core moral argument that motivated many philosophical ascetics. In brief, acts of deliberate self-denial are practice in an important part of acting ethically and are thus practically rational as a means to acquiring virtue. And if this argument has been a core motivation for asceticism in the West then arguably philosophical ascetics have been on to something, especially given contemporary empirical research on self-control.